Influence of spray drying conditions on the properties of whole goat milk. Issue 6 (31st March 2021) - de Oliveira, Aparecida Helena; Mata, Mario Eduardo R. M. Cavalcanti; Fortes, Mauri; Duarte, Maria Elita Martins; Pasquali, Matheus; Lisboa, Hugo M.
Abstract: Goat milk is still an underexploited product, mainly due to technical hurdles. Conversion into powder by spray drying can ensure product quality and safety, but un-optimized processing causes losses on product value. Therefore, our work intended to study the effects of spray drying on goat milk powder using fundamental parameters. A set of 12 experiments were conducted by varying outlet temperature, and feed flow rate so different drying kinetics were tested. The process presented yields ranging from 41 to 62.5%, benefitting from lower relative humidity conditions. Also, drying gas relative humidity close to 1% in combination with smaller droplets produced powders with higher density, lower color alterations, and lower variations on the chemical content of the powdered milk. Finally, it is concluded that the feed flow rate is a critical process parameter because it influences droplet size and relative humidity.